REFORESTATION / Greening Community participation in disaster management landslide (JURNAL SPASIAL, 2017)
Greening is in need, by the choice of plants, forest rejuvenation, establish community forests. It also includes the manufacture of building erosion control, with the aim to preserve land. In its management, watershed should be seen as a unified land resource. So let wise watershed management based on the relationship between human needs and the availability of resources to meet the human needs. Watershed management usually refers to the management of the two anasirnya (component) which is considered the most important, namely land and water resources. As for the other elements, such as climate, vegetation, relief and humans, is needed as factors in the management of. Community participation in watershed management is very helpful for the landslide disaster mitigation community participation can be expected through a few things, one of them did penenam trees / reforestation gontong together, and the other is also expected that the community in order to maintain the environment around the residence with attention to environmental cleanliness. do not throw garbage in the gutter or the yard of the house, those things that could be considered to mitigate landslides.